Kesantunan Tuturan dalam Kolom Komentar Akun Twitter Felixsiauw - Hayari, Rima (UIR PRESS, 2022)
his research is motivated by the variety of language politeness carried out on Twitter social media accounts, especially on Felixsiauw's account. This makes the writer interested in conducting research on speech politeness in the comments column of Felixsiauw's twitter account. The problem in this research is how politeness is in the comments column of Felixsiauw's twitter account. The purpose of this study is to explore and collaborate on the politeness scale of twitter users' comments on Felixsiauw's twitter account. The data source in this study is the comment column on Felixsiauw's twitter account on May 6, 2020 and January 14, 2021. This study uses a qualitative approach and uses the method of content analysis. Data collection techniques are documentation techniques, listening techniques, note-taking techniques. The results of this study found 120 data in total. On the scale of losses and gains, there are 24 data which are dominated by polite speech. On the choice scale there are 15 data which are dominated by polite speech. On the indirectness scale, there are 56 data which are dominated by impolite speech. On the authority scale, there are 3 data which are dominated by polite speech. On the social distance scale, there are 22 data which are dominated by polite speech. Most of the utterances found on the indirectness scale were the least found on the authoritative scale. In this study, research findings regarding the Leech scale were obtained, namely the authority scale and social distance scale. For the authority scale, it is difficult to know whether someone has the same social rank as Felixsiauw or not. For the social distance scale, there is difficulty in knowing whether someone has close social distance or not based on their comments. This is because the research data is in the form of comments on social media